Long-Wave High-Frequency Oscillations in Ionic Crystals with Two Atoms in Elementary Cell - Stupka, A. A. (Ukrainian Journal of Physics, 2018)
Long-wave high-frequency electromagnetic oscillations in an ionic crystal with two atoms in an elementary cell have been considered in the framework of a self-consistent model for free point charges in the electromagnetic field in a dielectric medium. The frequency of longitudinal phonons is shown to equal the ionic plasma frequency divided by the square root of the high-frequency dielectric permittivity. The standard dispersion law for the upper phonon-polariton branch is obtained.